Optimal reinforcement for improving the thermal performance of a permafrost tunnel based on coupled heat-mass transfer - Li, Shuangyang; Li, Gen; Wang, Chong; Lai, Yuanming; Yang, Jiale; Zhang, Jing (Tunnelling and underground space technology, 2022)
•A coupled model was proposed to simulate heat-mass transfers in a permafrost tunnel.•The heat and mass transfers of Fenghuoshan permafrost tunnel were well described.•An optimization method was proposed to improve thermal performance of the permafrost tunnel. Over 80% of cold-region tunnels (CRTs) suffer from heavy periodic freeze–thaw actions, and therefore, their normal safe operations cannot be guaranteed. To mitigate freeze–thaw damage to CRTs, thermal insulation layers (TILs) were used to prevent external heat from penetrating the surrounding rock of CRTs. TILs were often laid between two linings of CRTs with a uniform thickness along the whole tunnel based on a single thermal conduction calculation or engineering analogy method, which was not only uneconomical but also unsafe. Thus, freeze–thaw damage still occurred at the entrance of the CRTs. To solve this engineering problem, we took the Fenghuoshan Tunnel in permafrost regions as an example and proposed a coupled heat-mass transfer model based on mass, energy and momentum conservation principles. The numerical model was indicated to be accurate by comparing the computed and monitored temperatures. The subsequent numerical results show that the heat and mass exchanges between the air inside the tunnel and tunnel wall make the air velocities vary with seasonal alternation, and therefore, temperatures of the surrounding permafrost exhibit evident differences on the temporal and spatial scales, according to which the most unfavorable position and time point are selected to design an optimal reinforcement for improving the thermal performance. Based on a series of heat-mass transfer simulations with different thicknesses of aerogel felt, an optimal changeable thickness of aerogel felt along the whole tunnel is obtained to improve the thermal performance of the Fenghuoshan Tunnel. If the permafrost tunnel is reinforced by this approach, the highest temperatures of the surrounding permafrost near the tunnel are less than approximately −0.44 °C, implying that the optimal reinforcement is effective and can control the freeze–thaw damage of the Fenghuoshan Tunnel. This study provides theoretical support for designing a safe and economical reinforcement on permafrost tunnels and understanding the coupled heat-mass transfer processes in tunnels.